Wet Chemical and UV-Vis Spectrometric Iron Speciation in Quenched Low and Intermediate Level Nuclear Waste Glasses. Issue 1744 (2015) - Weaver, Jamie L.; Wall, Nathalie A.; McCloy, John S.
ABSTRACT: In this study wet chemical methods combined with UV-Vis spectroscopy were performed to quantify Fe(II)/Fe(III) ratios and total iron content of quenched alkali alumino-boro-silicate (simulated nuclear waste) glasses, applying a colorimetric method. We report lessons learned from experimental challenges encountered associated with the colorimetric method, where 1, 10 phenanthroline method is complexed with dissolved glass powder and the resulting solution measured for absorbance at 520 nm to determine Fe(II). To obtain total iron, the solution was then equilibrated with a mild reducing agent to chance all Fe to Fe(II), and the absorbance measured again at 520 nm. These absorbance values allowed for calculation of the Fe(II)/Fe(III) ratio, and the total iron content in the glasses. Total Fe measured is somewhat higher than as-batched target values for waste glasses, but very accurate for reference BCR-2G glass. All quenched alumino-boro-silicate glasses analyzed showed a Fe(II)/Fe(III) ratio between 0.06 (± 0.01) and 0.04 (± 0.01). These values are consistent with those obtained for similar glass compositions melted under analogous conditions, indicating a composition of ca. 94-96% Fe(III).